2003
DOI: 10.1016/s0002-9440(10)63548-1
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of Pathology in the Investigation of Bioterrorism-Related Cutaneous Anthrax

Abstract: Cutaneous anthrax is a rare zoonotic disease in the United States. The clinical diagnosis traditionally has been established by conventional microbiological methods, such as culture and gram staining. However, these methods often yield negative results when patients have received antibiotics. During the bioterrorism event of 2001, we applied two novel immunohistochemical assays that can detect Bacillus anthracis antigens in skin biopsy samples even after prolonged antibiotic treatment. These assays provided a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
60
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 50 publications
3
60
0
1
Order By: Relevance
“…53,54 The drug rFVIII may enable enhancing coagulation in patients with anthrax who exhibit severe hemorrhage and coagulopathy, as described in clinical settings. [9][10][11][12]31 To develop an effective treatment against anthrax, combining other anti-anthrax agents with a coagulation intervention strategy may be a feasible approach. Figure 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…53,54 The drug rFVIII may enable enhancing coagulation in patients with anthrax who exhibit severe hemorrhage and coagulopathy, as described in clinical settings. [9][10][11][12]31 To develop an effective treatment against anthrax, combining other anti-anthrax agents with a coagulation intervention strategy may be a feasible approach. Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, the reason both clinical and animal studies have revealed that hemorrhagic disorder is one of the major manifestations of LT-treated or B. anthracis-infected hosts remains unclear. [7][8][9][10][11][12][13] Recent studies have shown that LT might contribute to hemorrhage by inducing thrombocytopenia and megakaryocytic suppression. [14][15][16] The mechanism underlying coagulation suppression, however, remains undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we showed that LT enhances vascular cell adhesion molecule-1 (VCAM-1) expression and monocyte adhesion on the surface of tumor necrosis factor-␣ (TNF)-activated primary human endothelial cells, suggesting a possible link between LT and the vasculitis associated with anthrax (9,22,23). The enhanced expression of VCAM-1 was found to be transcriptionally driven by the cooperative activation of the VCAM1-regulating transcription factors, interferon regulatory factor-1 (IRF-1), and NF-B (24).…”
mentioning
confidence: 99%
“…Interestingly, others have claimed the pathologic damage after exposure to the LT occurs independently from any change in expression of cytokines (see Moayeri et al, 2003). Guarner et al (2003) suggested that the toxic effects of LT might be caused by hemorrhage, pleural effusion, and vasculitis. Vascular dysfunction is an important component in the pathogenesis of anthrax, although the underlying cause of this dysfunction is not yet known (Cui et al, 2004;Fritz et al, 1995;Shieh et al, 2003).…”
Section: Discussionmentioning
confidence: 99%